PEMBENTUKAN INSTITUSI PENGAJIAN TINGGI BERTERASKAN WAKAF DI MALAYSIA: CADANGAN MODEL PELAKSANAANNYA: The Establishment of a Waqf-Based Higher Educational Institution in Malaysia: Proposed Model for Implementation - Mahamood, Siti Mashitoh; Ab Rahman, Asmak; Che Seman, Azizi (Jurnal Syariah, 2018)
The article discusses the establishment of higher educational institution using waqf instrument. It suggests a model for the establishment to be applied in waqf-based higher education institutions in Malaysia based on the existing legislations and the contemporary needs. The model has used the research data collected from some international Waqf and Endowment Universities which had been carried out from 2012-2017.